Continuous Vaginal Bleeding Induced By EGFR-TKI in Premenopausal Female Patients With EGFR Mutant NSCLC - Yu, Min; Li, Xiaoyu; Wu, Xueqian; Wang, Weiya; Li, Yanying; Zhang, Yan; Zhang, Shuang; Wang, Yongsheng (Frontiers in Oncology, 2022)
EGFR-TKI is widely used for EGFR-mutant NSCLC patients. Bleeding is reported as a neglected adverse effect induced by EGFR-TKI. Female patients with lung adenocarcinoma have a high frequency of EGFR mutations. This study investigated the effect of EGFR-TKI on the menstrual cycle, especially on bleeding, in women of childbearing age. The underlying mechanism was further investigated in a patient with severe bleeding. We retrospectively investigated the effects on menstrual cycle in premenopausal female NSCLC patients who underwent EGFR-TKI treatment during 2013 to 2019. Menstrual changes including cycle disorders and prolonged bleeding were investigated via questionnaire survey. EGFR signaling, ER, PR and tissue factor expression were analyzed in endometrium tissue obtained from a 43-year-old patient who suffered from continuous vaginal bleeding during treatment with erlotinib and osimertinib. Among 42 premenopausal female patients taking EGFR tyrosine kinase inhibitor, 69.05% patients experienced abnormal menstruation. In women with abnormal menstruation, 41.37% had profuse menstruation and 20.69% had irregular menstruation. In the typical case, abnormal vaginal bleeding stopped when suspending EGFR-TKI, or reduced markedly following tamoxifen or progestogen administration. The EGFR-TKI induced abnormal vaginal bleeding is associated with low progesterone level, decreased EGFR activation and tissue factor (TF) expression in endometrial tissues. EGFR-TKI unusually induce abnormal vaginal bleeding in premenopausal female NSCLC patients, which may be attributed to progesterone/EGFR/TF signaling. Megestrol acetate may be an available and effective drug for the uncommon adverse effect.